The economic impacts of carbon emission trading scheme on building retrofits: A case study with U.S. medium office buildings. (1st August 2022) - Lou, Yingli; Yang, Yizhi; Ye, Yunyang; He, Chuan; Zuo, Wangda
Abstract: As a popular emission reduction tool, the carbon emission trading scheme (ETS) can potentially add an economic incentive for building owners to retrofit buildings in addition to the cost savings in energy. However, the additional economic benefits of building retrofits brought by ETS has not been quantitively investigated yet. To fill this gap, this study proposed a systematic economic evaluation method to investigate the economic impacts of ETS on building retrofits. The reduction of the payback period and the increase of the return on investment are adopted as evaluation metrics. Using medium office buildings as an example, this study predicted the economic impacts of ETS on building retrofits at four locations in the U.S., and three different carbon prices were investigated. The results show that carbon prices have significant economic impacts on building retrofits. With the relatively low forecasted time-variant carbon prices (around 10 USD per ton), the economic impacts of ETS on building retrofits are small. When carbon prices increase, the impacts of ETS would be up to 25% for 50 USD per ton (current prices in European Union) and 51% for 100 USD per ton. Furthermore, locations with more fossil energy have higher relative changes in the payback period and ROI but are more sensitive to carbon prices. Highlights: Carbon trading increases the return on investment of building retrofits. Carbon prices have significant economic impacts on building retrofits. The impacts of carbon trading are up to 25% using current price in European Union. Carbon trading generates more benefits in locations with more fossil energy. Locations with more fossil energy are more sensitive to carbon prices.